Overview of (1→3)-β-D-glucan immunobiology - David L. Williams (Mediators of Inflammation)
Glucans are (1→3)-β-D-glucose polymers that are found in the cell wall of fungi, bacteria and plants. Glucans are known to stim ulate humoral and cell-mediated immunity in humans and animals. In addition to the potent immune stimulatory effects of (1→3)-β-D-glucans, there are a number of toxicological effects associated with exposure to the water-insoluble, microparticulate form of the polymer. Recent investigations have suggested a potential role for (1→3)-β-D-glucans in inhalational toxicity. Specifically, (1→3)-β-D-glucans have been implicated in the symptomatology associated with ‘sick building’ syndrome. The mechanisms by which (1→3)-β-D-glucans mediate immune stimulation and, perhaps, toxicity are currently under investigation. It is now established that (1→3)-β-D-glucans are recognized by macrophages and, perhaps, neutrophils and natural killer cells via a (1→3)-β-glucan specific receptor. Following receptor binding, glucan modulates macrophage cytokine expression. Here we review the chemistry, immunobiology and toxicity of (1→3)-β-D-glucans and how it may relate to effects caused by inhalation.